A new lysosome-targetable fluorescent probe for detection of endogenous hydrogen polysulfides in living cells and inflamed mouse model. (1st November 2019) - Liang, Li; Li, Weiqing; Zheng, Jinrong; Li, Ruixi; Chen, Haiyan; Yuan, Zhenwei
Abstract : H2 S n play significant roles in maintaining biological homeostasis in organisms. In this work, a new fluorescent probe PP-PS was designed for detecting endogenous H2 S n . The probe has good properties and was applied in living cancer cells and tissues. Abstract : Hydrogen polysulfides (H2 S n, n > 1) belong to sulfane sulfur in the reactive sulfur species (RSS) family and play significant roles in maintaining biological homeostasis in organisms. The detection of H2 S n in living systems is essential, but further understanding of its "intact" function in living cells has been limited, owing to the lack of appropriate analytical tools. In this work, a new fluorescent probe PP-PS was designed for the detection of endogenous H2 S n . The probe has a large Stokes shift (178 nm), low detection limit (1 nM), and short response time (1 minute). Besides, PP-PS was successfully applied in the imaging of endogenous H2 S n in lysosomes of living cancer cells, xenograft mouse tumor tissues, and LPS-induced mouse inflammation tissues. These results revealed that the probe PP-PS could act as a new fluorescence imaging tool to study the function of intracellular hydropolysulfides.